NUANSA ISLAM DALAM GERAKAN PETANI TANGERANG 1924 - Ilyas Ilyas (IAIN Syekh Nurjati Cirebon, 2018)
AbstractThe study is a study of farmers living in colonial times, taking place in the Tangerang region in the first half of the 20th Century. As one of the land that became private land, Tangerang is controlled by some rich landowners. They control the land and all the objects that are on it. Absolute mastery gave birth to resistance coming from the peasants of Tangerang. This article seeks to discuss the elements of Islam that exist in the resistance carried out by the farmers of Tangerang. From the study, it can be seen that the nuances of Islam seen in the 1924 Tangerang peasant movement are in the coronation of the movement's leaders, eschatogical concepts, prayers to God, tabaruk with pilgrimage, and wearing white clothes.Keywords: movement farmer, private land, landlord, Tangerang